Analysis and Innovation for Penetrant Testing for Airplane Parts. (2015) - Guirong, Xu; Xuesong, Guan; Yuliang, Qiao; Yan, Gao
Abstract: Whether the helicopter or the aerotransport, NDT methods are used in the development phase, manufacture phase, use phase and maintenance phase. Especially penetrant testing is the efficient measure. We confirm the parts which do the penetrant testing according to the load in the development phase; Have penetrant testing after the working procedure which produce the defects in manufacture phase; Have penetrant testing for the area which use the big load in use phase. We must ensure the validity of penetrant testing in every phase. The arrangement of penetrant procedure, surface prepare of machine parts, protection of on-working parts, these are all the problems in the practice working. We analysis and innovate these problems, halve the experience with the other NDT technicians.